Supersensitivity induced by the toxin of Brazilian scorpion venom (Tityus serrulatus Lutz e Mello) - Antonio, A.; Melito, I.; Almeida, A. P.; Corrado, A. P. (Elsevier, 1976)
The purified toxin of the Brazilian scorpion venom (TsTX) enhances the pharmacological actions of directly and indirectly acting substances on several preparations. The enhancing action of TsTX is more pronounced for the indirectly acting drugs, which is highly suggestive of a prejunctional site of action. Secondarily, TsTX does also produce an unspecific increase of sensitivity at the level of the pharmacological receptor itself. The mechanism by which these changes are brought about remains to be determined. © 1976.